Surface modification of plant-based microparticles for colloidal science and cellular adhesion applications - Tan, Ee-Lin (2019)
Pollen microparticles and sporopollenin - sporoderm microcapsules (S-SMCs) provide a compelling all-natural solution for use in a wide range of oil/water emulsion-type applications. To enhance the utility of pollen microparticles and S-SMCs, surface modification was shown to be a mechanism for altering surface chemistry and thereby tuning microparticle wetting properties, emulsification characteristics, and particle/cell adhesion. This project explored the extraction and surface modification of discrete pollen particles from bee-collected pollen granules and the extraction of S-SMCs from pollen particles. Characterization of the ultraviolet-ozone (UV-O) surface modified particles (pollen and S-SMCs) by X-ray photoelectron spectroscopy (XPS) and attenuated total reflectance Fourier transform infrared (ATR-FTIR) to give insight to the UV-O modifications to sporopollenin (both native and acid extracted). This project will also be exploring the possible applications for such microparticles as functional microbeads. UV- O treatment is shown to increase the proportion of surface elemental oxygen and C=O bonds, leading to enhanced particle dispersion properties, control over Pickering emulsion characteristics, and increased particle/cell binding affinities. Looking forward, bee-collected pollen is widely available, competitively priced, and is considered regulation-free for oral consumption due to a long history of use as a food and medicine, with extensive literature purporting numerous health benefits. Beyond facilitating the utilization of pollen and S-SMCs as a functional microparticle system, a greater understanding of UV-O surface modification of sporopollenin also provides insights into the inherent UV protective properties of pollen shells, and provides insights into the use of pollen sporopollenin for exploring climate change through fossil records.